Six years’ experience of laparoscopic varicocelectomy using bipolar electrosurgery and its effect on semen parameters - Karami, Hossein; Hassanzade Hadad, Amin; Fallahkarkan, Morteza (Urology Journal, 2016)
Purpose: To evaluate postoperative results of laparoscopic varicocelectomy using bipolar electrosurgery and analyze semen according to the grade of varicocele after surgery. Materials and Methods: In a six-year period, 416 men with clinical varicocele and impaired semen parameters or infertility underwent laparoscopic varicocelectomy using bipolar electrosurgery. All patients were assessed for hydrocele and recurrence of varicocele six months and one year after the procedure. Semen analyses were obtained before and after the surgery and were compared according to the clinical grade of varicocele. Results: Seven patients (1.7%) had right side, 391 (94%) had left side and 18 (4.3%) had bilateral varicoceles. Varicocele grades I, II and III were detected in 113 (27.1%), 232 (55.7%) and 71 (17%) patients respectively. Abdominal wall emphysema and pneumoscrotum were developed in 19 (4.5%) and 11 (2.6%) cases. Recurrence rate was significantly higher in grade III varicocele (P < .001). In patients with varicocele grades of I and II, sperm concentration, motility and morphology significantly improved six months after surgery (P < .05). In patients with grade III varicocele, only sperm concentration improved (P < .05). Sperm motility and morphology did not show any significant change after one year. Conclusion: Laparoscopic varicocelectomy using bipolar cautery is a safe, feasible and cost-effective technique with few complications. It significantly improves sperm parameters. A follow up program for at least one year after the surgery seems reasonable to detect recurrent cases. The study shows that increase in clinical varicocele grade can cause irreversible deleterious effects on sperm motility and morphology. So, earlier treatment is recommended.